[Computed tomographic measurement of coronary artery calcification in the assessment of cardiovascular risk: a descriptive study]. - Morcillo, C; Valderas, J; Roca, J; Oliveró, R; Núñez, C; Sánchez, M; Bechich, S (2007)
INTRODUCTION AND OBJECTIVES: Measurement of coronary artery calcification (CAC) is used in the evaluation of cardiovascular risk. We investigated its usefulness by comparing CAC assessment with that of various risk charts. METHODS: We determined cardiovascular risk in patients without known atherosclerosis using the 1998 European Task Force (ETF), REGICOR (Registre Gironí del Corazón) and SCORE (Systematic Coronary Risk Evaluation) charts. CAC was assessed by computerized tomography and measurements were classified as low risk (i.e., score <1), intermediate risk (i.e., score 1-100), or high risk (i.e., score >100). RESULTS: The study included 331 patients (mean age 54 [8.5] years, 89% male). In 44.1%, CAC was detected (mean score 96 [278]). The degree of agreement between the cardiovascular risk derived from the CAC score and that derived from the SCORE and ETF charts was acceptable: kappa=.33 (P<.05) and kappa=.28 (P<.05), respectively, but agreement was poor with the REGICOR chart: kappa=.02 (P=.32). The SCORE and ETF charts, respectively, classified 45.0% and 38.3% of patients with a CAC score >100 as high risk, whereas the REGICOR chart did not classify any of these patients as high risk. Male sex, older age, smoking history, and a family history of coronary heart disease were all associated with the detection of CAC. CONCLUSIONS: Measurement of CAC demonstrated calcification in 44.1% of patients without known atherosclerosis. By regarding those with a CAC score > 100 as high-risk, 10.4% of patients evaluated using the SCORE chart would be reclassified as high risk, as would 11.6% of those evaluated using the ETF chart, and 18.9% of those evaluated using the REGICOR chart. Consequently, more patients would be eligible for preventative treatment.